Measuring the contours of the global knowledge economy with a digital index - Ojanpera, S; Graham, M; Straumann, R; De Sabbata, S (Oxford Department of International Development, University of Oxford, 2016)
Our Digital Knowledge Economy Index, combines traditional data sources with bespoke data on capacities and skills (measured via content-creation and participation on digital platforms) to provide a revealing view of where developing countries fit into the world’s digital knowledge economy.